2021
DOI: 10.4142/jvs.2021.22.e78
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of recurrent subclinical mastitis in cows caused by enrofloxacin resistant bacteria by means of the sequential intramammary infusion of enrofloxacin HCl-2H2O and ceftiofur HCl: a clinical trial

Abstract: Background Recurrent subclinical mastitis (RScM) due to resistant bacteria has low clinical and bacteriological cure rates, often requiring the culling of cows. The sequential intra-mammary administration of enrofloxacin hydrochloride-dihydrate (enro-C) followed by ceftiofur HCl may be useful for treating these cases. Objectives This study assessed the bacteriological and clinical cure-efficacies of the sequentially intramammary administration of enro-C, followed by cef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The antibiotic (in the form of hydrochloride dihydrate) was administered twice daily for 5 days via intramammary infusions (infusions into the udder) at a dose of 300 mg. The authors showed that 65% of cattle treated with enrofloxacin recovered, while the additional introduction of ceftiofur-HCl led to a 100% recovery [ 68 ].…”
Section: Efficacy Of Enrofloxacin In Veterinary Medicinementioning
confidence: 99%
“…The antibiotic (in the form of hydrochloride dihydrate) was administered twice daily for 5 days via intramammary infusions (infusions into the udder) at a dose of 300 mg. The authors showed that 65% of cattle treated with enrofloxacin recovered, while the additional introduction of ceftiofur-HCl led to a 100% recovery [ 68 ].…”
Section: Efficacy Of Enrofloxacin In Veterinary Medicinementioning
confidence: 99%
“…Most of the substances are typically used intramammary, some can also be administered systemically. Fluoroquinolones can also be applied systemically for treatment of S. aureus mastitis (Alfonseca‐Silva et al., 2021 ).…”
Section: Assessmentmentioning
confidence: 99%
“…In general, SEB is considered in literature as a potent biological weapon with incapacitating effects (Ahanotu et al, 2006;Bhaskar and Sant, 2020). It is one out of 25 currently characterised staphylococcal enterotoxins and has its toxic effect from its ability to function as a superantigen, toxins able to evoke an immune response of large proportions, commonly resulting in food poisoning and flulike symptoms that can lead to multi-organ failure and death (Bhaskar and Sant, 2020).…”
Section: Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…It has a pH of 6.5 in suspension at 30 mg/mL and achieves high concentrations in mammary tissue. Enro-C has shown high success in treating uncomplicated cases of mastitis [ 10 11 12 ] and recurrent chronic cases caused by bacteria resistant to fluoroquinolones [ 13 ].…”
Section: Introductionmentioning
confidence: 99%